Nontraded goods and the balance of trade in a neo-Keynesian temporary equilibrium - Neary, J (John Wiley & Sons, 1980)
This paper explores the implications for international monetary economics of recent work on macroeconomic models of temporary equilibrium with rationing. A model of a small open economy is presented, which, though fully consistent in the long run with the monetary approach to the balance of payments, behaves very differently in the short run when the wage and the price of nontradeables are sticky. Among the comparative statics properties of the model are the following: a devaluation may not improve the trade balance; a wage cut may not increase employment; and technological progress has different effects, depending on the sector in which it occurs.